Traditional Indian Medicines Used for the Management of Diabetes Mellitus. (5th June 2013) - Rizvi, Syed Ibrahim; Mishra, Neetu
Abstract : Plants have always been a source of drugs for humans since time immemorial. The Indian traditional system of medicine is replete with the use of plants for the management of diabetic conditions. According to the World Health Organization, up to 90% of population in developing countries use plants and its products as traditional medicine for primary health care. There are about 800 plants which have been reported to show antidiabetic potential. The present review is aimed at providing in-depth information about the antidiabetic potential and bioactive compounds present in Ficus religiosa, Pterocarpus marsupium, Gymnema sylvestre, Allium sativum, Eugenia jambolana, Momordica charantia, and Trigonella foenum-graecum . The review provides a starting point for future studies aimed at isolation, purification, and characterization of bioactive antidiabetic compounds present in these plants.